2020
DOI: 10.2147/dmso.s236966
|View full text |Cite
|
Sign up to set email alerts
|

<p>Relationship Between Self-Care Behavior and Cognitive Function in Hospitalized Adult Patients with Type 2 Diabetes: A Cross-Sectional Study</p>

Abstract: These authors contributed equally to this workPurpose: To investigate the relationship between diabetes self-care behavior and cognitive function of hospitalized young and middle-aged Chinese patients with type 2 diabetes mellitus (T2DM). Patients and Methods:In this cross-sectional study, young and middle-aged T2DM patients (age range, 35-65 years) were recruited at 4 tertiary hospitals between July 2016 and January 2017. Data pertaining to self-care behavior and cognitive function were collected using two qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
3
6
0
1
Order By: Relevance
“…More than two‐thirds (68.8%) of the patients had not checked their feet or inspected the inside of their shoes every day. Our findings are consistent with those of previous studies demonstrating poor foot care performance in patients with T2DM (Ausili et al, 2017; Guo et al, 2012; Yang et al, 2020). A combination of actions (e.g., providing foot care education and training) should be taken by health‐care providers to promote greater self‐initiated foot care in Chinese patients with T2DM (Coffey et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More than two‐thirds (68.8%) of the patients had not checked their feet or inspected the inside of their shoes every day. Our findings are consistent with those of previous studies demonstrating poor foot care performance in patients with T2DM (Ausili et al, 2017; Guo et al, 2012; Yang et al, 2020). A combination of actions (e.g., providing foot care education and training) should be taken by health‐care providers to promote greater self‐initiated foot care in Chinese patients with T2DM (Coffey et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, self‐care performance varies for diet, exercise, blood sugar testing and foot care (Ausili et al, 2017; Kav et al, 2017; Nicolucci et al, 2013). For example, the least frequently performed self‐care activities were exercise and foot care in patients in Italy and Bangladesh (Ausili et al, 2017; Saleh et al, 2014), whereas the Chinese patients with T2DM had the poorest performance on foot care and blood sugar testing (Guo et al, 2012; Yang et al, 2015, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the study, executive function was not associated with DSMQ-R total or other subscale scores for diet, glucose management, and physical activity. Previous studies have found that, in adults with T2D, scores for executive function were positively associated with overall DSMB (Gatlin & Insel, 2015; Primožič et al, 2012; Thabit et al, 2009) or with specific DSMB such as diet and glucose management (Cuevas & Stuifbergen, 2017), medication management (Tran et al, 2014), and foot care (Cuevas & Stuifbergen, 2017; Yang et al, 2020). This inconsistency may be attributable to the fact that most participants in this study had normal cognitive functions and perceived themselves to have good cognitive functions.…”
Section: Discussionmentioning
confidence: 98%
“…No que tange às comorbidades e complicações ligadas ao diabetes mellitus, as variáveis referentes à presença de hipertensão arterial sistêmica e de dislipidemia apresentaram associação às atitudes negativas relacionadas com o autocuidado. Sugere-se que pessoas com hipertensão e dislipidemia se cuidam menos em relação à alimentação, tabagismo e ao exercício físico (18) . A dislipidemia e hipertensão são frequentemente associadas e representam cerca de 50% do risco de desenvolvimento de doença arterial coronariana (19) .…”
Section: Discussionunclassified